Pengenalan Citra Sidik Jari Menggunakan Metode Principal Component Analysis dan Hamming Distance - Samuel Lukas; Meiliayana Meiliayana; Gunawan Sugianto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2007)
Each person has a unique fingerprint and many research have been conducted to recognize thesefingerprints. Many applications have also been implemented related to fingerprint matching. This paperdiscusses on how good the Principal Component Analysis (PCA) which is combined with Hamming distance inrecognizing five fingerprints.Some experiments are conducted to get what is the best number of PCA vector in recognizing the fivehuman fingerprints data. The result of these experiments are also reported in this paperinally, the results of allexperiments are also be reported.Keywords: Principal Component Analysis, finger print, Hamming distance.